PENGARUH INTERAKSI ANTARA PROJECT BASED LEARNING DAN DIRECT INSTRUKSIONAL SERTA GAYA KOGNITIF TERHADAP KEMAMPUAN PEMECAHAN MASALAH MAHASISWA - Atti Yudiernawati; Tavip Dwi Wahyuni; Pudji Suryani (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT Problem-solving ability is a fundamental competency that university students must possess to meet the demands of analysis and decision-making in professional contexts. The development of this ability is influenced not only by the learning strategies applied but also by individual cognitive characteristics. This study aims to examine the effects and interaction between Project Based Learning and Direct Instruction models and students’ cognitive styles on problem-solving ability. The research employed a quasi-experimental approach with a 2×2 factorial design involving 87 students from the Health Promotion Study Program. Cognitive styles were classified into field independent and field dependent using the Group Embedded Figure Test, while problem-solving ability was assessed through scenario-based tests. The data were analyzed using two-way ANOVA. The findings indicate that students taught using Project Based Learning demonstrated higher problem-solving ability compared to those taught using Direct Instruction. In addition, students with a field independent cognitive style performed better than those with a field dependent style. Further analysis revealed a significant interaction between learning models and cognitive styles. These findings suggest that the effectiveness of learning strategies in enhancing problem-solving ability depends on the alignment between instructional approaches and students’ cognitive characteristics. ABSTRAK Kemampuan pemecahan masalah menjadi kompetensi esensial bagi mahasiswa dalam menghadapi tuntutan analisis dan pengambilan keputusan di dunia profesional. Pengembangan kemampuan ini tidak hanya dipengaruhi oleh strategi pembelajaran yang digunakan, tetapi juga oleh karakteristik kognitif individu. Penelitian ini bertujuan untuk mengkaji pengaruh serta interaksi antara model pembelajaran Project Based Learning dan Direct Instruction dengan gaya kognitif mahasiswa terhadap kemampuan pemecahan masalah. Penelitian menggunakan pendekatan quasi-experimental dengan rancangan faktorial 2×2 yang melibatkan 87 mahasiswa Program Studi Promosi Kesehatan. Gaya kognitif diklasifikasikan menjadi field independent dan field dependent menggunakan Group Embedded Figure Test, sedangkan kemampuan pemecahan masalah diukur melalui tes berbasis skenario. Data dianalisis menggunakan two-way ANOVA. Hasil penelitian menunjukkan bahwa mahasiswa yang mengikuti Project Based Learning memiliki kemampuan pemecahan masalah yang lebih tinggi dibandingkan dengan Direct Instruction. Selain itu, mahasiswa dengan gaya kognitif field independent menunjukkan performa yang lebih baik dibandingkan field dependent. Analisis lebih lanjut mengungkap adanya interaksi signifikan antara model pembelajaran dan gaya kognitif. Temuan ini menegaskan bahwa efektivitas pembelajaran dalam meningkatkan kemampuan pemecahan masalah bergantung pada kesesuaian antara strategi pembelajaran dan karakteristik kognitif mahasiswa.